Mathematical Communication Skills Reviewed From Mathematical Resilience in Independent Learning and Discovery Learning Assisted by E - Learning (Universitas Negeri Semarang, 2021)
This research aims to describe mathematical communication skill from mathematical resilience in independent learning assisted by module and discovery learning assisted by e-learning. This mixed – method research took population from X graders of SMA N 6 Cirebon. The sampling technique was purposive sampling. The results were X MIPA 4 as experimental group 1 (intervened by independent learning assited by module) and X MIPA 6 as experimental group II (intervened by discovery learning assited by e-learning). The subject categorization was based on mathematical resilience with high, moderate, and low categories. The instruments of this research were mathematical resilience questionnaire, mathematical communication skill test, and interview. The results showed that independent learning assited by module and discovery learning assisted by e-learning were effective. There was no difference mathematical communication skill between independent learning assisted by module and discovery learning assisted by e-learning on average. The descriptions of the students’ mathematical communication skills reviewed from mathematical resilience were varied.